Bradyrhizobium diazoefficiens USDA 110 displays plasticity in the attachment phenotype when grown in different soybean root exudate compounds - Sandhu, Armaan Kaur; Brown, McKenzie Rae; Subramanian, Senthil; Brözel, Volker S. (Frontiers in Microbiology, 2023)
Bradyrhizobium diazoefficiens, a symbiotic nitrogen fixer for soybean forms nodules after developing symbiotic association with the root. For this association bacteria need to move towards and attach to the root. These steps are mediated by surface and phenotypic cell properties of bacteria and secreted root exudate compounds. Immense work has been done on nodule formation and nitrogen fixation, but little is known about the phenotype of these microorganisms under influence of different root exudate chemical compounds (RECCs) and how this phenotype impacts root attachment ability. To address this gap in knowledge, we studied the impact of twelve different RECCs, one commonly used carbon source, and soil extracted solubilized organic matter (SESOM) on attachment and attachment related properties of B. diazoefficiens USDA110. We measured motility related properties, (swimming, swarming, chemotaxis, flagellar expression), attachment and related properties (surface hydrophobicity, biofilm formation, attachment to cellulose and soy roots), and surface polysaccharidal properties (colony morphology, exopolysaccharide quantification, lectin binding profile, lipopolysaccharide profiling). We found that USDA 110 displays a high degree of surface phenotypic plasticity when grown on the various individual RECCs. Some of the RECCs played specific roles in modulating the motility and root attachment processes. Serine increased cell surface hydrophobicity and root and cellulose attachment, with no EPS formed. Gluconate and lactate increased EPS production and biofilm formation, while decreasing hydrophobicity and root attachment, and raffinose and gentisate promoted motility and chemotaxis. Results also indicated that the biofilm formation trait on hydrophilic surfaces (polystyrene) cannot be related to attachment ability of Bradyrhizobium to the soybean root. Among the tested phenotypic properties, bacterial cell surface hydrophobicity was the one with significant impact on root attachment ability. We conclude that USDA 110 displays plasticity of surface property and attachment phenotype determined by individual RECCs from the soybean. Conclusions made based on its behavior in standard carbon sources such as arabinose or mannitol do not hold for its behavior in soil.